Pengetahuan Mahasiswa Biologi Mengenai Penerapan Bioteknologi Rekayasa Genetika Ditinjau Dari Perspektif Islam - Abdul Hadi (Kopertais Wilayah I DKI Jakarta dan Banten, 2021)
Advances in science and technology encourage the economic, industrial, and health sectors to develop rapidly through diagnostic and therapeutic treatments. Therapeutic-based health research encourages the advancement of modern biotechnology to answer all medical problems. However, not infrequently, advances in modern biotechnology are often considered contrary to moral, ethical, social, legal, psychological and religious values. The presence of biotechnology is considered to dominate human life and has great power to change the development of living organisms and creates an interesting condition to study and analyze when it is associated with the management of medical biotechnology products that are safe for the environment, people's lives and religion. This study aims to determine the level of knowledge of Biology students at X & Y universities regarding the application of genetic engineering biotechnology when viewed from an Islamic perspective and the relationship of knowledge to Biology students' attitudes about genetic engineering using qualitative data research through planning (antecedents), processes (transactions), and results (outcomes). The results of the study of 60 biology students from universities X and Y obtained 8 students X and 7 students Y had knowledge of genetic engineering in an Islamic perspective. Meanwhile, after all students participated in the discussion session and were given articles on genetic engineering in an Islamic perspective, all students agreed that the application of genetic engineering must be based on religious knowledge so that research was carried out in accordance with the rules contained in the MUI fatwa No. 35 of 2013.